Transcriptional Profiling of Porcine HCC Xenografts Provides Insights Into Tumor Cell Microenvironment Signaling - Patel, Shovik S.; Sandur, Amitha; El-Kebir, Mohammed; Gaba, Ron C.; Schook, Lawrence B.; Schachtschneider, Kyle M. (Frontiers in Genetics, 2021)
Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related death worldwide, representing the most common form of liver cancer. As HCC incidence and mortality continue to increase, there is a growing need for improved translational animal models to bridge the gap between basic HCC research and clinical practice to improve early detection and treatment strategies for this deadly disease. Recently the Oncopig cancer model—a novel transgenic swine model that recapitulates human cancer through Cre recombinase induced expression of KRASG12D and TP53R167H driver mutations—has been validated as a large animal translational model for human HCC. Due to the similar size, anatomy, physiology, immunology, genetics, and epigenetics between pigs and humans, the Oncopig has the potential to improve translation of novel diagnostic and therapeutic modalities into clinical practice. Recent studies have demonstrated the importance of tumor cells in shaping its surrounding microenvironment into one that is more proliferative, invasive, and metastatic; however, little is known about the impact of microenvironment signaling on HCC tumor biology and differential gene expression between HCC tumors and its tumor microenvironment (TME). In this study, transcriptional profiling was performed on Oncopig HCC xenograft tumors (n=3) produced via subcutaneous injection of Oncopig HCC cells into severe combined immunodeficiency (SCID) mice. To differentiate between gene expression in the tumor and surrounding tumor microenvironment, RNA-seq reads originating from porcine (HCC tumor) and murine (microenvironment) cells were bioinformatically separated using Xenome. Principle component analysis (PCA) demonstrated clustering by group based on the expression of orthologous genes. Genes contributing to each principal component were extracted and subjected to functional analysis to identify alterations in pathway signaling between HCC cells and the microenvironment. Altered expression of genes associated with hepatic fibrosis deposition, immune response, and neoangiogenesis were observed. The results of this study provide insights into the interplay between HCC and microenvironment signaling in vivo, improving our understanding of the interplay between HCC tumor cells, the surrounding tumor microenvironment, and the impact on HCC development and progression.